Difficulties in emotional regulation as a predictor of fear of missing out on events (FOMO) in a sample of adolescents with anorexia nervosa disorder - Marewan Hasan Mustafa; Shahzad Ramadan Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The aim of this current research is to reveal the possibility of predicting fear of missing out on events (FOMO) through the factor of emotional regulation difficulties in a sample of adolescents with anorexia nervosa disorder. And measure the differences according to the variable: (sex). The research relied on the analytical descriptive approach. The researcher used the FOMO scale and the Difficulty Emotional Regulation Scale (DERS). The research sample included (176) male and female general secondary students who have anorexia nervosa disorder. The results of the research were: It is possible to predict through the difficulties of emotional regulation the fear of missing out on events (FOMO) in a sample of adolescent high school students who have anorexia nervosa disorder. And there are statistically significant differences between the mean scores of the research sample's answers on the emotional regulation difficulties scale according to the gender variable in favor of female students. There are significant differences on the scale of fear of losing juveniles in favor of females.